The theory of economic planning - Heal, G. M. (Amsterdam : North-Holland Pub. Co. ; New York : American Elsevier Pub. Co., 1973)
Emphasis is on viewing the economic system as a whole: the problems studied are those that arise at the level of the system rather than at the level of its constituent parts. The author confines the book to a number of general theoretical issues concerning the operation and properties of planned economic systems, and to discuss such economies at something approaching the degree of abstraction at which traditional welfare economics has discussed the behavior of a competitive economy.
Volume III.
Includes index.
Includes bibliographical references: p. 399-403.
rpm 11/10/2017
Loans
Keywords: Economic policy